Where Do I Go from Here? Sensemaking and the Construction of Growth-Based Stories in the Wake of Denied Promotions - Vough, Heather C.; Caza, Brianna Barker (Academy of Management Review, 2017)
Denied promotions occur when individuals go up for but do not receive promotions at work. The extant literature focuses on the negative implications of denied promotions. We argue, in contrast, that individuals can ultimately benefit from denied promotions and experience positive outcomes when they construct growth-based stories about the event. Drawing on a sensemaking perspective, we articulate when individuals are likely to construct growth-based denied promotion stories, highlighting the identity and social conditions that support such stories. We then link growth-based denied promotion stories to the positive behavioral outcomes of work engagement and career proactivity via increases in resilience in their career identities. Finally, we situate denied promotions in the broader context of the career and address how responses to denied promotions are influenced by past responses to career setbacks and may shape future responses to career setbacks. Our model provides theoretical contributions to the literature on denied promotions, careers, positive organizational scholarship, and sensemaking.